Association between cholesterol and blood pressure examination in Sampangan, Semarang City: a preliminary study - Christyana, To Lidwina Prillya Indra; Riwanto, Ignatius; Sebong, Perigrinus H; Sutanto, Eviana Budiartanti; Ernestia, Henrita; Tjitradinata, Cynthia; Kristanti, Alberta Widya (Universitas Gadjah Mada, 2023)
Purpose: This study aims to determine the baseline prevalence and association between blood pressure and cholesterol examination. Method: This preliminary study used a cross-sectional design to analyze the secondary blood pressure and cholesterol levels data in the Sampangan sub-district, Semarang City. The total sampling technique covered those enrolled in the metabolic syndrome screening from January to April 2023. The logistic regression test was used in data analysis. Results: 58 respondents took blood pressure checks, while only 40 had cholesterol checks. The probability of males getting changes in cholesterol levels was higher than that of females (OR = 8.69; p-value = 0.01). However, neither (female nor male) had a significant relationship, and there was no difference in the chances of changes in blood pressure (OR = 1.43; p = 0.72). Respondents above 60 years had a significant association with changes in blood pressure compared to those under 60 years (OR = 0.09; p = 0.007). Conclusion: This study revealed males of a certain age experience higher changes in cholesterol levels compared to females. People over 60 years old tend to have higher blood pressure compared to those under 60 years old. These findings propose an outreach strategy for health screening for patients with limited mobility, transportation access, and finances for routine checkups at public or government healthcare facilities.